2016
DOI: 10.3389/fped.2016.00110
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Maintenance Therapy in Childhood Acute Lymphoblastic Leukemia: The Experience of the Prospective, Randomized Brazilian GBTLI ALL-93 Protocol

Abstract: AimMaintenance therapy is an important phase of the childhood ALL treatment, requiring 2-year long therapy adherence of the patients and families. Weekly methotrexate with daily 6-mercaptopurine (6MP) constitutes the backbone of maintenance therapy. Reduction in the maintenance therapy could overweight problems related with poverty of children with ALL living in limited-income countries (LIC).ObjectiveTo compare, prospectively, the EFS rates of children with ALL treated according to two maintenance regimens: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…According to the last Brazilian cancer incidence data, approximately 3000 children (up to 19 years of age) are diagnosed with ALL annually ( Estimativa 2018, 2017 ). Brazilian children enrolled in prospective cooperative clinical trials achieve survival rates comparable to those reported by centres in Western Europe and North America ( Ribeiro et al, 2007 ; Möricke et al, 2010 ; Silverman et al, 2010 ; Hunger et al, 2012 ; Brandalise et al, 2010 , Brandalise et al, 2016 ). ALL treatment is based fundamentally on combination chemotherapy.…”
Section: Introductionsupporting
confidence: 58%
“…According to the last Brazilian cancer incidence data, approximately 3000 children (up to 19 years of age) are diagnosed with ALL annually ( Estimativa 2018, 2017 ). Brazilian children enrolled in prospective cooperative clinical trials achieve survival rates comparable to those reported by centres in Western Europe and North America ( Ribeiro et al, 2007 ; Möricke et al, 2010 ; Silverman et al, 2010 ; Hunger et al, 2012 ; Brandalise et al, 2010 , Brandalise et al, 2016 ). ALL treatment is based fundamentally on combination chemotherapy.…”
Section: Introductionsupporting
confidence: 58%
“…The referring physicians provided information about the demographic and clinical follow up data for the patients. Patients were not formally enrolled in treatment protocols, but were treated according to either the Brazilian Group for Treatment of Childhood Leukemia (GBTLI-ALL99) or the Berlin-Frankfurt-Munster ALL (BFM–ALL) backbone protocols (14, 15).…”
Section: Methodsmentioning
confidence: 99%
“…Laks et al published in 2003 that a probability of 5‐year OS was 56.5% in a cohort from Rio Grande do Sul 22 . The GBTLI ALL‐93 study showed a probability of 15‐year EFS of 53.8% in HR patients 19 . Lustosa de Sousa et al in 2015 described the results of a cohort from 3 hospitals in Ceará.…”
Section: Discussionmentioning
confidence: 99%